Impacts of Energy Subsidy Reforms on the Industrial Energy Structures in the Malaysian Economy: A Computable General Equilibrium Approach - Yusoff, Nora Yusma Bte Mohamed; Bekhet, Hussain Ali (International Journal of Energy Economics and Policy, 2016)
The objective of this study is to analyze the effects of fuel subsidy removal on the industrial energy structures, which are crude oil, natural gas and coal, electricity and gas and petroleum products. A computable general equilibrium model and social accounting matrix for the Malaysian economy in 2005 are employed. Simulations based on different groups of scenarios (removing fuel subsidies, energy tax subsidies and both fuel subsidies and energy tax subsidies) were developed. The results showed that the fuel and tax subsidy reform policy had a stronger effect on energy consumption structures, which successfully reduced total energy consumption by 3.56%. This meant that removing fuel and tax subsidies could increase the potential energy savings by 1,286.35 ktoe. On the other hand, the higher fossil fuel price due to the subsidy removal encouraged the utilization of alternative energy, and consequently reduce dependency on fossil fuel. The energy subsidy reform policy not only significantly reduced the amount of the fossil fuel consumption, but simultaneously improved the real GDP and fiscal deficit in the government’s budget. Importantly, the study concluded that the energy subsidy reform policy was found to be an efficient policy mechanism that supported the National Energy Efficiency Master Plan for 2010, as well as supported utilization of "fifth fuel” policy under the Malaysian Fuel Diversification Policy. Keywords: Fuel subsidy, tax subsidy, industrial energy structures, computable general equilibrium, macroeconomic performance, Malaysia. JEL Classifications: H2, Q43